Enteric-coated sodium bicarbonate supplementation improves high-intensity cycling performance in trained cyclists - Hilton, N. P.; Leach, N. K.; Hilton, M. M.; Sparks, S. A.; McNaughton, L. R. (European Journal of Applied Physiology, 2020)
Purpose: Enteric-coated sodium bicarbonate (NaHCO3) can attenuate gastrointestinal (GI) symptoms following acute bicarbonate loading, although the subsequent effects on exercise performance have not been investigated. The purpose of this study was to examine the effects of enteric-coated NaHCO3 supplementation on high-intensity exercise performance and GI symptoms. Methods: Eleven trained male cyclists completed three 4 km time trials after consuming; a placebo or 0.3 g/kg body mass NaHCO3 in enteric-coated or gelatin capsules. Exercise trials were timed with individual peak blood bicarbonate ion concentration ([HCO3-]). Blood acid-base balance was measured pre-ingestion, pre-exercise, and post-exercise, whereas GI symptoms were recorded pre-ingestion and immediately pre-exercise. Results: Pre-exercise blood [HCO3-] and potential hydrogen (pH) were greater for both NaHCO3 conditions (P < 0.0005) when compared to placebo. Performance time was faster with enteric-coated (- 8.5 ± 9.6 s, P = 0.044) and gelatin (- 9.6 ± 7.2 s, P = 0.004) NaHCO3 compared to placebo, with no significant difference between conditions (mean difference = 1.1 ± 5.3 s, P = 1.000). Physiological responses were similar between conditions, although blood lactate ion concentration was higher with gelatin NaHCO3 (2.4 ± 1.7 mmol/L, P = 0.003) compared with placebo. Furthermore, fewer participants experienced GI symptoms with enteric-coated (n = 3) compared to gelatin (n = 7) NaHCO3. Discussion: Acute enteric-coated NaHCO3 consumption mitigates GI symptoms at the onset of exercise and improves subsequent 4 km cycling TT performance. Athletes who experience GI side-effects after acute bicarbonate loading may, therefore, benefit from enteric-coated NaHCO3 supplementation prior to exercise performance.